2017
DOI: 10.1093/mnras/stx632
|View full text |Cite
|
Sign up to set email alerts
|

Narrow phase-dependent features in X-ray dim isolated neutron stars: a new detection and upper limits

Abstract: We report on the results of a detailed phase-resolved spectroscopy of archival XMM-Newton observations of X-ray Dim Isolated Neutron Stars (XDINSs). Our analysis revealed a narrow and phase-variable absorption feature in the X-ray spectrum of RX J1308.6+2127. The feature has an energy of ∼740 eV and an equivalent width of ∼15 eV. It is detected only in ∼ 1/5 of the phase cycle, and appears to be present for the entire timespan covered by the observations (2001 December -2007. The strong dependence on the pulsa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
7
34
0
Order By: Relevance
“…There is also another feature at lower energy (∼ 2 keV) at phase ∼ 0.5, which, if significant, may be just a continuation of the main feature (this is supported by the line width evolution but not by the line energy evolution, see the two upper panels of Fig.11). A similar phase and energy dependent feature has been detected so far only in two sources: the low-B magnetar SGR 0418 (see T13) and the X-ray dim isolated neutron star RX J0720.4-3125 (see Borghese et al 2015). s in these sources the feature may be due to proton-cyclotron resonant scattering of X-ray photons emitted by the star surface onto charges flowing in a small coronal magnetic loop (for alternative interpretations see the discussion in T13 and Borghese et al 2015).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…There is also another feature at lower energy (∼ 2 keV) at phase ∼ 0.5, which, if significant, may be just a continuation of the main feature (this is supported by the line width evolution but not by the line energy evolution, see the two upper panels of Fig.11). A similar phase and energy dependent feature has been detected so far only in two sources: the low-B magnetar SGR 0418 (see T13) and the X-ray dim isolated neutron star RX J0720.4-3125 (see Borghese et al 2015). s in these sources the feature may be due to proton-cyclotron resonant scattering of X-ray photons emitted by the star surface onto charges flowing in a small coronal magnetic loop (for alternative interpretations see the discussion in T13 and Borghese et al 2015).…”
Section: Resultssupporting
confidence: 71%
“…A similar phase and energy dependent feature has been detected so far only in two sources: the low-B magnetar SGR 0418 (see T13) and the X-ray dim isolated neutron star RX J0720.4-3125 (see Borghese et al 2015). s in these sources the feature may be due to proton-cyclotron resonant scattering of X-ray photons emitted by the star surface onto charges flowing in a small coronal magnetic loop (for alternative interpretations see the discussion in T13 and Borghese et al 2015). The energy variation of the line would be caused by magnetic field gradients along the coronal loop: as the neutron star rotates, photons directed toward us intercept sections of the loop with different magnetic field intensities.…”
Section: Resultssupporting
confidence: 71%
“…This discrepancy may be due to large magnetic fields of these XDINSs. In fact, XDINSs commonly have absorption feature in the X-ray spectrum [102,103], which is interpreted as the proton cyclotron resonance or atomic transition. Both require the magnetic field larger than about 10 13 G, and such a strong magnetic field can affect the thermal evolution of XDINSs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the magneto-thermal evolutionary tracks computed by Viganò et al (2013) show that their observational characteristics are compatible with those expected from neutron stars born with dipolar field of a few 10 14 G after a few millions of years, a timespan consistent with the characteristic ages of XDINSs. Borghese et al (2015Borghese et al ( , 2017 inspected the phase resolved spectra of all XDINSs and found in two of them narrow phase-dependent absorption features that, if interpreted as proton cyclotron lines, akin in SGR 0418+5729, indicate the presence close to the star surface of nondipolar magnetic field components ≈10 times stronger than the values derived from the timing parameters, tightening the links between XDINSs and magnetars.…”
Section: Persistent Emission and Spectral Featuresmentioning
confidence: 98%